Hip Election Radiographic Plane In Total Hip Prostheses With Femoral Neck Preservation - A, Palermo; A, Casabella; M, Formica; L, Molfetta (Journal of Medical Biomedical and Applied Sciences, 2018)
Background: In the preoperative planning of the hip prosthesis the radiography of the pelvis on which to plan the surgery remains the routine exam which helps the surgeon to make a correct implant; however, in some institutes, there are 2D-3D instruments and computerized navigators, which are able to plan the surgery. Dedicated radiographs can show the neck, on which to plan the level of subcutaneous resection (isthmus), the size of the component, the correction of the leg lenghtening.Material & Method: the Hip Election Radiographic Plane (HERP) of the hip is a particular radiographic projection âdedicatedâ to the best view of femoral neck, important for a correct planning of the implant with neck preservation. The x-ray, performed with a device that links the pelvis and not only the lower limb with the rigid hip, allows the entire femoral neck to be extracted in its chosen plane. A sample of 20 patients underwent standard X-ray and HERP X-ray, and then compared the planning data with the implant.Results: the result concerning preoperative planning on standard X-ray and on HERP X-ray highlights the greater reliability of the second about the identification of the isthmus and the choice of the size.Conclusions: the research of the HERP is the âdedicatedâ planning for the wnp prostheses, but useful for every other type of prosthetic femoral component, to make a plant as correct as possible